Arbitration in the 36th America's Cup [electronic resource] including additional previously unpublished material - Peter, Henry (Kluwer Law International, 2022)
"Arbitration in the 36th America⁰́₉s Cup is the fifth of a series with a unique corpus of all decisions by the 36th America⁰́₉s Cup Arbitration Panel, including all supporting documents elucidating the context in which the decisions were issued. More than the most prestigious regatta and match race in the sport of sailing, the America⁰́₉s Cup is a test of boat design, sail design, and management skills. It is not surprising that its passionate skippers, builders, and managers often become embroiled in disputes. Recognizing the need to deal quickly and professionally with any divergency, an arbitration panel has become an established part of the Cup's organization" --